2014
DOI: 10.1099/vir.0.060624-0
|View full text |Cite
|
Sign up to set email alerts
|

Interference with jasmonic acid-regulated gene expression is a general property of viral suppressors of RNA silencing but only partly explains virus-induced changes in plant–aphid interactions

Abstract: The cucumber mosaic virus (CMV) 2b viral suppressor of RNA silencing (VSR) inhibits host responses to jasmonic acid (JA), a chemical signal regulating resistance to insects. Previous experiments with a CMV subgroup IA strain and its 2b gene deletion mutant suggested that VSRs might neutralize aphid (Myzus persicae) resistance by inhibiting JA-regulated gene expression. To further investigate this, we examined JA-regulated gene expression and aphid performance in Nicotiana benthamiana infected with Potato virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 36 publications
5
46
0
Order By: Relevance
“…In these TuMV-infected plants, it was found that deposition of callose (which has defensive properties against aphids) was decreased and the levels of certain amino acids were elevated in the phloem sap and that these changes were attributable to the TuMV NIa-Pro (Casteel et al, 2014). In contrast, Westwood et al (2014) found that infection of N. benthamiana plants with PVY decreased the reproduction of Myzus persicae although the growth of the individual aphids placed on the infected plants was not inhibited. Although transgenic expression of the PVY HC-Pro in N. benthamiana inhibited jasmonic acid-induced plant gene expression (a potential anti-insect defense) and enhanced aphid reproduction, it was concluded that this viral factor is not the predominant determinant of virus-induced effects on aphid-plant interactions during infection (Westwood et al, 2014).…”
Section: Molecular Determinants Of Aphid-mediated Transmission and Homentioning
confidence: 79%
See 1 more Smart Citation
“…In these TuMV-infected plants, it was found that deposition of callose (which has defensive properties against aphids) was decreased and the levels of certain amino acids were elevated in the phloem sap and that these changes were attributable to the TuMV NIa-Pro (Casteel et al, 2014). In contrast, Westwood et al (2014) found that infection of N. benthamiana plants with PVY decreased the reproduction of Myzus persicae although the growth of the individual aphids placed on the infected plants was not inhibited. Although transgenic expression of the PVY HC-Pro in N. benthamiana inhibited jasmonic acid-induced plant gene expression (a potential anti-insect defense) and enhanced aphid reproduction, it was concluded that this viral factor is not the predominant determinant of virus-induced effects on aphid-plant interactions during infection (Westwood et al, 2014).…”
Section: Molecular Determinants Of Aphid-mediated Transmission and Homentioning
confidence: 79%
“…In contrast, Westwood et al (2014) found that infection of N. benthamiana plants with PVY decreased the reproduction of Myzus persicae although the growth of the individual aphids placed on the infected plants was not inhibited. Although transgenic expression of the PVY HC-Pro in N. benthamiana inhibited jasmonic acid-induced plant gene expression (a potential anti-insect defense) and enhanced aphid reproduction, it was concluded that this viral factor is not the predominant determinant of virus-induced effects on aphid-plant interactions during infection (Westwood et al, 2014). Currently, it is not known if BCMV or BCMNV alter the behavior or performance (survival, growth, or reproduction) of aphids on infected bean plants.…”
Section: Molecular Determinants Of Aphid-mediated Transmission and Homentioning
confidence: 79%
“…Attenuated expression of JA‐responsive genes was previously reported for transgenic Nicotiana benthamiana plants expressing the HC‐Pro silencing suppressor that is employed by many potyviruses (Westwood et al . ), including SMV (Lim et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced performance of E. varivestis larvae on SMV-infected plants, and the corresponding feeding preferences of adult beetles, may reflect the suppression of endogenous JA levels by SMV infection. Attenuated expression of JA-responsive genes was previously reported for transgenic Nicotiana benthamiana plants expressing the HC-Pro silencing suppressor that is employed by many potyviruses (Westwood et al 2014), including SMV (Lim et al 2011). As noted above, SMV-infected leaf tissues also had the highest levels of sugars of any treatment, along with increased levels of free amino acids in leaves, which are known feeding stimulants (Lapidus et al 1963;Augustine et al 1964).…”
Section: S I N G L E I N F E C T I O N B Y S M Vmentioning
confidence: 95%
“…Signaling pathways controlling these plant responses to microbial infection operate through the action of phytohormones like jasmonic acid (JA). During viral infection, however, JA-regulated gene expression is rather suppressed by RNA silencing (Hanks et al, 2005;Westwood et al, 2014). As a consequence, virus-infected plants may be more susceptible to secondary bacterial or fungal infections.…”
Section: Resultsmentioning
confidence: 99%